Uncharted strait : the future of China-Taiwan relations - Bush, Richard C., 1947- (Washington, D.C. : Brookings Institution Press, 2013)
'Focuses on cross-Strait relations during Ma Ying-jeou's first term, assessing the impact of stabilization on economics, politics, and security and the implications for resolution of Taiwan and China's fundamental dispute. Examines how Taiwan can strengthen itself; how China can promote a mutually acceptable outcome; and how Washington can protect its interests in South Asia'--Provided by publisher.
Includes bibliographical references (pages 251-308) and index.
Keywords: Taiwan -- Relations -- China; China -- Relations -- Taiwan